Experimental analysis of density fingering instability modified by precipitation - Binda, Leonardo David (2017)
We analyze the effect of precipitate formation on the development of density induced hydrodynamic instabilities. In this case the precipitate is BaCO3, obtained by reaction of CO2 with aqueous BaCl2. CO2(g) dissolution increases the local density of the aqueous phase, triggering Rayleigh ?Taylor instabilities and BaCO3 formation. It was observed that at first the precipitate was formed at the finger front. As the particles became bigger, they began to fall down from the front. These particles were used as tracers using PIV technique to visualize the particle streamlines and to obtain the velocity of that movement. This falling produced a downwards flow that might increase the mixing zone. Contrary to expectations, it was observed that finger length decreased, indicating that for the mixing zone development, the consumption of CO2 to form the precipitate is more important than the downwards flow. The mixing zone length was recovered increasing the availability of the reactant (higher CO2 partial pressure), compensating the CO2 used for BaCO3 formation. Mixing zone development rates reached constant values at shorter times when the precipitate is absent than when it is present. An analysis of the non linear regime with and without the precipitate is performed.